Prognostic Factors for Clinical Response in Systemic Lupus Erythematosus Patients Treated by Allogeneic Mesenchymal Stem Cells - Lihui Wen; Myriam Labopin; Manuela Badoglio; Dandan Wang; Lingyun Sun; Dominique Farge-Bancel (Stem Cells International)
Systemic lupus erythematosus (SLE) is an autoimmune disease with a broad range of clinical manifestations and a heterogeneous disease course. There is no cure for SLE, but current standard pharmacotherapies can improve disease prognosis in most patients. However, some patients are refractory to conventional treatments and require alternative treatment options. The present study is aimed at identifying predictors of clinical response to allogeneic bone marrow-derived or umbilical cord-derived mesenchymal stem cell (BM-/UC-MSC) transplant in SLE. All adult patients identified in the Nanjing database with an SLE Disease Activity Index (SLEDAI) score≥8 at baseline that had undergone MSC transplant and who had at least 1 year of follow-up after one or two successive intravenous injections of allogeneic BM-/UC-MSCs (1 million/kg) were analyzed. SLE symptoms and SLEDAI were assessed at baseline and during follow-up to determine low disease activity (LDA) and clinical remission (CR) at 1, 3, 6, and 12 months. Sixty-nine patients were included in the study, with a median (range) SLEDAI of 13 (8-34) at baseline. Among the 69 patients, 40 (58%) achieved LDA and 16 (23%) achieved CR with a SLEDAI of 9 (4–20), 8 (0-16), 6 (0-18), and 5 (0-18) after 1, 3, 6, and 12 months, respectively. Older age (p=0.006) and no arthralgia/arthritis at baseline (p=0.03) were associated with a higher rate of LDA. Achieving CR was associated with older age (p=0.033), no arthralgia/arthritis at baseline (p=0.001), and no prior use of cyclophosphamide (p=0.003) or hydroxychloroquine (p=0.016). Future studies using unique immunosuppressive regimens and allogeneic MSC sources will further elucidate determinants of clinical response to MSC transplant in SLE.